"It's Beautiful to be Old." In Search of Emergent Catholic Social Teaching on Old Age. (29th November 2018) - Kevern, Peter
Abstract: The proportion of older people in the population is rapidly increasing, both nationally and globally. This demographic shift poses some pressing practical challenges for governments as they seek to provide care for an ageing population; but in addition, it raises sociocultural and theological questions about how the role and significance of older people is understood in contemporary developed economies. In response to these challenges, the present paper attempts to identify the outlines of an emerging Catholic Social Teaching on old age in the encyclicals and words of the last three popes. Two key themes are identified which inform a distinctive Catholic perspective on old age. These are the continuing pilgrimage, role and contribution of older people to the end of life on the one hand, and their challenge to the values of a 'throwaway culture' on the other. The foundational significance of these themes for an emerging Catholic witness form the basis for the concluding recommendations.